Pattern of coagulation in pediatric and adult multiple trauma patients (Annals of Medical Research, 2021)
Aim: Aim of this study was evaluated changes in coagulation parameters in adult and pediatric multiple trauma patients.Material and Methods: A prospective observational study was conducted of adult and pediatric patients with blunt multiple trauma. The platelet count, prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT), fibrinogen, D-dimer, tissue factor (TF), factor VII and factor X were evaluated.Results: For our pediatric trauma patients, platelet count, factor VII and factor X were inversely related to the APACHE II score, whereas aPTT, D-dimer and INR and APACHE II scores were positively correlated. Furthermore, we found that aPTT, D-dimer, INR and TF in adults positively correlated with the APACHE II score. We also found that factor X, aPTT, and platelet count were strongly associated with adverse outcomes in pediatric trauma patients, and remained independently associated in the multivariate analysis. Conclusion: TF and INR are strongly associated with adverse outcomes after multiple traumas in adults. However, in pediatric patients, platelet count, aPTT, TF and factor X are associated with adverse outcomes. Therefore, early assessment of TF and INR in adult trauma patients, and platelet count, aPTT, TF and factor X in pediatric trauma patients, may significantly improve the accuracy of assessments of the severity of traumatic injuries.
Keywords: Coagulopathy; clotting factors; posttraumatic coagulopathy; trauma.